Evaluasi Ergonomi Operator Mesin Pembuatan Adonan Mie dalam Upaya Mengurangi Risiko Pekerja - Hanafie, Ahmad; Haslindah, Andi; Andrie, Andrie; Haslinah, Andi (Department of Electrical Engineering, University of Patria Artha, 2021)
Work postures that are less than ideal will pose a risk that can be caused by injury or body disorders that cause fatigue that arises very quickly. Complaints that arise due to work facilities that are not ideal so that they are not ergonomic have an impact on workers feeling less comfortable, in the end it results in decreased worker productivity. The research objective can provide a solution by evaluating ergonomics with a nordc body map analysis approach with an anthropometric approach, research methods with direct observation and descriptive statistical analysis and anthropometric analysis with the 95th percentile. The results obtained using an anthropometric approach with ideal work equipment placement include height of place the material is 102.5 cm, the working position between the material and the machine is 142.4 cm, and the distance between the material and the machine and operator is 68.8 cm. It has a very significant impact on the operator with the average complaint from the Nordic body map analysis, which is 3.65 which was previously only below the ideal, which was 2.68 on average. with a change in operator is able to increase work productivity.